Evaluation of the Effect of Lymph Node Status on the Survival of Non-Small Cell Lung Cancer Patients With Brain Metastases: Applications of a Novel Grade Prognostic Assessment Score Model Involving N Stage - Zhu, Jianfei; Wang, Wuping; Xu, Shuonan; Jia, Chenghui; Zhang, Qingqing; Xia, Yanmin; Wang, Wenchen; Wen, Miaomiao; Wang, Xuejiao; Wang, Hongtao; Zhang, Zhipei; Cai, Ling; et al. (Frontiers in Oncology, 2020)
Background: Grade prognostic assessment (GPA) was widely used to evaluate the prognosis of non small cell lung cancer (NSCLC) patients with brain metastases (BM).This study was designed to investigate whether lymph node status (LNS) can be involved as one of GPA variables in NSCLC with BM. Methods: Overall, 586 NSCLC patients with BM were analyzed retrospectively. Overall survival stratified by LNS was analyzed by Kaplan-Meier method. We also performed multivariate analysis to identity the independent prognostic factor by Cox proportional hazards progression model. In the updated GPA index, prognosis factors and criteria of GPA score were weighted by effect magnitude relative risk (RR) and statistical significance. Results: In NSCLC patients with BM, comparing to patients without lymph nodes involvement, patients with lymph nodes involvement had worse overall survival (mOS, 13.4 months vs 25.9 months, P＜0.001). Multivariate analysis proved that LNS might be an independent prognostic factor (RR: 1.702, CI: 1.340-2.162, P＜0.001). Finally, five prognostic factors, including LNS, age of patient, KPS, number of BM and extracranial metastases were enrolled in our novel GPA index. With the updated GPA index involving N stage,survival analysis was also performed, the prognostic results were significant difference among these four subgroups (Class A vs Class B, P=0.047; Class B vs Class C, P≤0.001; Class C vs Class D, P=0.007). Conclusions: These results indicated that LNS might be an indispensable prognostic factor in NSCLC with BM, the novel GPA model involved by N stage could provide more reliable evidence to estimate survival for NSCLC patients with BM.